Kafka critique du monde social contemporain : les formes concretes de l’oppression de l’individu occidental - Brion, Charles (Labyrinth, 2025)
This article shows how the social criticism that unfolds in Kafka’s The Trial and then The Castle was able to guess the majority of the political ills of the contemporary West as they developed mainly from the 20th century onwards. Not restricting oneself to the usual analysis of oppression by the gigantic structures of justice and administration, it focuses more on concrete examples of mistreatment of the individual and underlines the major role of the complicity of admiring people of the totalitarian system. The servile citizens complete the aggression of the State by reducing the private sphere to a minimum. Certain more recent excesses of social networks, notably the growing confusion between the public sphere and the private sphere, are also announced by Kafka’s satire, which depicts the modern Westerner as denied his fundamental freedoms.